Innovative Agriculture Based on Islamic Economics in the Development of Farmer Groups Towards a Green Economy - Muhamad Aqim Adlan, Muhamad Aqim Adlan; Reza Ahmad Zahid; Labib Muzaki Shobir (Tribakti: Jurnal Pemikiran Keislaman, 2025)
This research aims to examine Islamic economics as a driver of creativity among farming groups in response to the green economy era. This is because the link between the agricultural sector and the green economy is relevant to achieving the balance of nature and the environment, which are fundamental values of Islamic economics. Islamic economics is intended to guide every policy and activity in the economic sector. Furthermore, the relationship between the economic sector and agriculture is inextricable when the agricultural sector's primary objective is to generate profit. This research uses a qualitative approach, drawing on primary and secondary data collected from farmer groups in the districts of Tulungagung, Trenggalek and Blitar, to examine their efforts to be creative. The collected data is presented descriptively and analysed using the concept of content analysis through the lens of Islamic economics. The findings of this study indicate that: (1) Strategies to increase the creativity of farmer groups in the Tulungagung, Trenggalek and Blitar regencies when facing green economy policies include implementing various innovative sustainable agricultural practices. (2) Implementing Islamic economic concepts to strengthen the creativity of farmer groups in these districts in the face of green economy policies has led to a significant transformation in agricultural practices. This research suggests the potential integration of Islamic economic principles as a normative basis for formulating sustainable agricultural policies, particularly in enhancing the creative capacity of farming communities to adapt to the challenges of the green economy era.